Effect of different oocytes recovery techniques on yield and quality oocyte from local caprine ovaries - H. AL-JIBOORI, NAHIDH; M. AL-RUBAEI, H. (Journal of Kerbala for Agricultural Sciences, 2017)
The objective of this research to study the effect of different oocytes recovery techniques on yield and quality of oocytes in local caprine ovaries. 180 ovaries were collected from adult and non-pregnant 90 females, slaughtered at abattoir of province of Babil during the period between April – November 2016, in an insulate container and transported to the laboratory within 2 hours. Oocytes were recovered by three techniques viz. slicing , puncture, and aspiration of follicle. Oocytes were categorized into three classes, first class: good quality oocytes with more than 3 layers of cumulus cells, second class: intermediate quality oocytes with less than 3 layers of cumulus cells, third class: poor quality oocytes, denuded oocytes from cumulus cells. The study showed that the total number of oocytes recovered and the number of oocytes recovered per ovary were significantly higher (P<0.05) in slicing (438 and 7.3±0.01 respectively) and punctures (384 and 6.4+0.88 respectively) compared to aspiration technique (243 and 3.9±0.20 respectively). The results of study also indicated that the total number of oocytes recovered, the number of oocytes recovered per ovary and the percentage of recovered oocyte for good quality oocytes were significantly higher (P<0.05) when using the slicing technique (275 , 4.58 and 62.87% respectively), and the puncture technique (202, 3.36 and 52.60% respectively) compared to aspiration technique (110 , 1.83 and 47.00% respectively). The results obtained suggested that the slicing method is the proper technique for recovering oocytes with good morphological aspects and quality.